Analysis of the Factors that Ensure the Possibility of Developing Economic Relations in the Field of Renewable Energy Between Ukraine and Turkey - Serhii Voitko; Olena Trofymenko; Saeb Moghaddamı (Journal of Economy Culture and Society)
Successful international economic activity in a particular technological sector is important for the further development of mutually beneficial socio-economic relations between neighboring countries. In order to implement the basic principles of this activity, it is necessary to determine the current level of cooperation between Turkey and Ukraine and the dynamics of its development, as well as to identify key factors influencing the development of cooperation in the field of renewable energy. The reasons for this study are the importance of ensuring effective cooperation between the two countries in the field of renewable energy, which requires an integrated approach. General scientific methods were used, the main of which are: system analysis – for determining the components of the system of foreign economic relations of Ukraine and Turkey in the direction of developing renewable energy; taxonomic analysis – for identifying factors influencing economic relations and determining their numerical value of the resulting indicator. The conducted study allowed us to evaluate the level of current developments in the direction of forging a strategic partnership and to explore the impact of stimulating and destimulating factors on the potential opportunities of both countries.